2004
DOI: 10.1117/1.1756596
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity indocyanine-green laser phototherapy of acne vulgaris: Pilot study

Abstract: Near infrared (NIR) diode laser low-intensity (soft) phototherapy with the topical application of indocyanine green (ICG) has been suggested for treatment of acne vulgaris. Twelve volunteers with acne lesions on their faces and/or backs were enrolled in the experiment. Skin areas of the subjects that were 4 x 5 cm2 were stained with ICG solution for 5 min before laser irradiation (803 nm) at a power density up to 50 mW/cm2 for 5 to 10 min. For 75% of the subjects, a single treatment was provided and for the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…[20] Indocyanine green (ICG), a NIR contrast agent with U.S. Food and Drug Administration (FDA) approval for clinical use, was applied to optical imaging of human vasculature [21,22] and treatments of skin diseases and cancers. [23,24] Not only with its high biocompatibility, has ICG also characterized with fluorescent excitation and emission at long wavelengths (ex: 800 nm; em: 820 nm) in NIR window, which minimize the intrinsic background interference. However, the photo (thermal)-degradation, high protein binding in the blood and aqueous-instability of free form ICG molecule limited its application as a fluorescence contrast agent for in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Indocyanine green (ICG), a NIR contrast agent with U.S. Food and Drug Administration (FDA) approval for clinical use, was applied to optical imaging of human vasculature [21,22] and treatments of skin diseases and cancers. [23,24] Not only with its high biocompatibility, has ICG also characterized with fluorescent excitation and emission at long wavelengths (ex: 800 nm; em: 820 nm) in NIR window, which minimize the intrinsic background interference. However, the photo (thermal)-degradation, high protein binding in the blood and aqueous-instability of free form ICG molecule limited its application as a fluorescence contrast agent for in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The selective photothermal action on the fat tissue can be implemented by the laser radiation wavelength choice using the absorption by the endogenous (own) tissue chromophores, in the present case the lipids contained in the fat drop of adipocytes, under the exposure to light with the wavelength 1210 nm [208]. However, with exogenous chromophores, e.g., the indocyanine green (ICG), the efficiency of light interaction with tissue may be essentially higher and more selective [209][210][211][212][213]. The intensity and position of ICG absorption peaks depend upon the solvents used [214][215][216].…”
Section: Photochemical and Photothermal Clearingmentioning
confidence: 99%
“…2 months following treatment without any adverse reactions [50]. A subsequent pilot study showed that for moderate-to-severe acne lesions, multiple treatments with a combination of ICG, and near infrared diode laser therapy were more effective than a single treatment session to improve the state of skin for a month without any side effects [51].…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%